Distantly Supervised Entity Relation Extraction with Adapted Manual Annotations - Sun, Changzhi; Wu, Yuanbin (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We investigate the task of distantly supervised joint entity relation extraction. It’s known that training with distant supervision will suffer from noisy samples. To tackle the problem, we propose to adapt a small manually labelled dataset to the large automatically generated dataset. By developing a novel adaptation algorithm, we are able to transfer the high quality but heterogeneous entity relation annotations in a robust and consistent way. Experiments on the benchmark NYT dataset show that our approach significantly outperforms state-ofthe-art methods.